Reduced Notch1 Cleavage Promotes the Development of Pulmonary Hypertension. Issue 1 (January 2022) - Wang, Shumin; Zhu, Guofu; Jiang, Dongyang; Rhen, Jordan; Li, Xiankai; Liu, Hao; Lyu, Yuyan; Tsai, Patrick; Rose, Yara; Nguyen, Tiffany; White, R. James; Pryhuber, Gloria S.; et al.
Abstract : Clinical trials of Dll4 (Delta-like 4) neutralizing antibodies (Dll4nAbs) in cancer patients are ongoing. Surprisingly, pulmonary hypertension (PH) occurs in 14% to 18% of patients treated with Dll4nAbs, but the mechanisms have not been studied. Here, PH progression was measured in mice treated with Dll4nAbs. We detected Notch signaling in lung tissues and analyzed pulmonary vascular permeability and inflammation. Notch target gene array was performed on adult human pulmonary microvascular endothelial cells (ECs) after inhibiting Notch cleavage. Similar mechanisms were studied in PH mouse models and pulmonary arterial hypertension patients. The rescue effects of constitutively activated Notch1 in vivo were also measured. We observed that Dll4nAbs induced PH in mice as indicated by significantly increased right ventricular systolic pressure, as well as pulmonary vascular and right ventricular remodeling. Mechanistically, Dll4nAbs inhibited Notch1 cleavage and subsequently impaired lung endothelial barrier function and increased immune cell infiltration in vessel walls. In vitro, Notch targeted genes' expression related to cell growth and inflammation was decreased in human pulmonary microvascular ECs after the Notch1 inactivation. In lungs of PH mouse models and pulmonary arterial hypertension patients, Notch1 cleavage was inhibited. Consistently, EC cell-cell junction was leaky, and immune cell infiltration increased in PH mouse models. Overexpression activated Notch1-attenuated progression of PH in mice. In conclusion, Dll4nAbs led to PH development in mice by impaired EC barrier function and increased immune cell infiltration through inhibition of Notch1 cleavage in lung ECs. Reduced Notch1 cleavage in lung ECs could be an underlying mechanism of PH pathogenesis. Abstract : Supplemental Digital Content is available in the text.